Metastatic erector spinae tumor underlying primary lung adenocarcinoma with paraneoplastic secreting beta-human chorionic gonadotropin hormone: A rare case report - Elsonmond Vick, Duin; Ravin, Prabaharan; Chan, Wai Hoong; Mohammad Zulkarnaen, Ahmad Narihan (2021)
Introduction: Beta-human chorionic gonadotropin (β-HCG) hormone is physiologically produced by syncytiotrophoblast cells in the placenta during pregnancy. It is also a specific marker for trophoblastic tumors of placenta and gestational tumors. In rare case, a rise in serum β-HCG may be due to ectopic secretion especially in epithelial carcinoma namely lung CA and other tumors. Here, we report a case of a middle-age woman presenting with rapid growing back swelling with amenorrhea and high serum β-HCG with underlying primary lung cancer. Discussion: 48 year-old single lady, ex-smoker and nulliparous presented with painful rapid growing back swelling for 3 months associated with marked loss of weight and appetite for 9 months. She was amenorrheic for 3 months. A firm mass located at left paraspinal area with 6x6cm in size, fixed to the underlying muscle and skin, irregular surface and border. Other systemic examinations was unremarkable. Serum β-HCG was high 1142mIU/ml. Transvaginal Ultrasonography was normal. Chest X-Ray showed consolidation over left middle zone of the lung. CT-TAP had left lung mass measuring 5.6x4.6x2.8cm with left hilar lymphadenopathy. MRI of whole spine revealed left erector spinae intramuscular lesion with adjacent inflammatory changes with no intraspinal extension. Tissue HPE showed fragments of fibrocollagenous tissue with malignant cell infiltration arranged in cords and glandular pattern. The malignant cells displayed mild pleomorphism with hyperchromatic nuclei and eosinophilic cytoplasm. Immunohistochemical study has positive CK7 and GATA3 with negative CK20 and TTF-1. These features are consistent with metastatic adenocarcinoma likely primary lung adenocarcinoma. Bronchoscopy-guided biopsy was performed and confirmed the diagnosis. She was then referred to oncology for further management. Conclusion: Ectopic secretion of β-HCG in lung carcinoma is not well understood and has not been well reported in literature. Therefore, such presentation may mimic various condition and this may result in delay of diagnosis. More studies are required for better understanding.